Developing a novel heuristic method to solve the unbalanced allocation problem - Faten Al-Obaidi; Alla Eldin Kassam; Sawsan Al-Zubaidi (Engineering and Technology Journal)
Globalization and technological advancements have emphasized the importance of efficient resource allocation for production, efficiency, cost reduction, and optimal use. The assignment problem, a long-term issue, has gained researchers' attention due to its significant impact on institutional success. It prioritizes resource allocation to minimize time and cost while ensuring the feasible execution of activities. The assignment issue can be balanced (the number of activities matches the number of resources) or unbalanced (the number of activities does not match the number of resources). This can lead to resources being left without assignments or activities without implementation when resources exceed activities. A novel heuristic method was proposed to allocate multiple activities to resources efficiently. The proposed method was unrelated to the Hungarian method and did not involve adding dummy tasks or machines. It was founded on lost opportunity cost, with all occupations implemented. The method was implemented numerically and showed a 7% reduction in total assignment time compared to the modified Hungarian method. It also reduced total idle time by 71% and increased machine utilization by 26%. The method's efficiency was further enhanced to evaluate the effectiveness of the proposed method by comparing results with the modified Hungarian method, demonstrating its practical relevance.